NEW FIVE DIMENSIONS OF GLOBAL SECURITY - Kukeyeva, F. T.; Zharylgasova, N. (International relations and international law Journal, 2016)
Authors analyses the new dimensions to global security. Analyses are based on the American experts’ research works. According to the American experts, in a globalized world, security can no longer be regarded as a zero sum game, with the state participation. Global security and the security of any country or culture cannot be achieved without good governance at all levels, ensuring security through justice for all people, nations and cultures